PENGARUH BAURAN PEMASARAN TERHADAP REPUTASI DAN CUSTOMER RELATIONSHIP MARKETING (CRM) SERTA DAMPAKNYA TERHADAP KEPUASAN PELANGGAN PADA BADAN PENYELENGGARA JAMINAN SOSIAL KETENAGAKERJAAN (BPJS) CABANG BELAWAN - Husaini Husaini; Nurdasila Darsono; T. Roli Ilhamsyah Putra (FEB - Unsyiah, 2018)
Social Security Agency (BPJS) Employment is one of the responsibilities and obligations of the State to provide social and economic protection to the public, in accordance with the conditions of the financial capabilities of the State. Program promotion is the primary channel for communicating a message to the participants, both existing participants and potential participants. This requires the parties to observe the Employment BPJS marketing strategies are most appropriate. The phenomenon underlying this study is due to the dissatisfaction of consumers or participants BPJS Employment services are still relatively low or participant is not satisfied. This is due to the incompatibility of the high expectations of customers to use services BPJS Employment Branch Medan Belawan. The population in this study were all participants Social Security Agency (BPJS) Employment Branch of Belawan, which reached 82,000 people. While the study sample was taken 150 participants. Sampling in this study conducted by convinience sampling technique. Data Analysis Method technique SEM (Structural Equation Modelling) operated by AMOS program 22. Results showed Promotion Mix, Brand Reputation, Customer Relationship Marketing (CRM) partially affect the Customer Satisfaction Social Security Agency (BPJS) Employment. The results also show that there is an indirect effect on the Promotion Mix Brand Reputation and also to Customer Relationship Marketing (CRM) at the Social Security Agency (BPJS) Employment